Patterns of Health Care Delivery Among Adults With Heart Failure in the Last Year of Life: A Retrospective Population‐Based Study - Hafid, Shuaib; Wills, Aria; Quinn, Kieran; Van Spall, Harriette; Fernandes, Aleisha; Chagani, Jehanara; Mak, Susanna; McGuinty, Caroline; Gallagher, Erin; Webber, Colleen; Bush, Shirley H.; Wentlandt, Kirsten; et al. (Journal of the American Heart Association)
People with heart failure (HF) are treated by multiple physician specialties as they approach the end of life (EOL). Patterns of physician involvement and health outcomes are not well understood. Elucidation of care patterns for this population may identify opportunities to minimize fragmentation and improve EOL continuity. This study describes categories of outpatient physician care patterns in the last year of life for people with HF and how EOL acute care use varies by category. We conducted a retrospective cohort study of 65 625 adults with HF (median age, 83 [interquartile range, 74-89] years; 44.2% women; 86.9% urban residents) who died between 2017 and 2019 in Ontario, Canada, using health administrative data. Individuals were categorized according to different combinations of outpatient care providers in the last year of life: (1) primary care, palliative care, and relevant specialties (25.9%); (2) primary care and palliative care (5.4%); (3) primary care and relevant specialties (40.8%); (4) primary care (18.6%); and (5) specialty care (9.3%). Primary care physicians maintained involvement throughout the last year of life, while the proportion of monthly palliative care encounters increased near death. People who had palliative care involvement had the lowest rates of hospitalization and acute care deaths compared with those without palliative care involvement. People with HF receive most outpatient care from primary care physicians and palliative care physicians at the EOL. Multiple specialties are involved, highlighting the patients' medical complexity. Findings may help inform ways to measure relational continuity at the EOL for patients with HF.